The elastoplastic numerical model and verification by macroindentation experiment of femoral head. Issue 14 (15th March 2021) - Wang, Jun; Yi, Chen; Wang, Sufang; Wang, Ling; Jia, Haiyou; Chen, Bo; Huan, Yong
Abstract: For internal fixation of proximal femoral fractures, a screw is commonly placed into the femoral head; therefore, mechanical matching of the femoral head and screw is important. This article proposes an elastoplastic numerical model of the femoral head that takes nonlinear deformation and cancellous bone heterogeneity into account. Force–depth curves from finite element analysis based on the model were compared with those from macroindentation experiments. The maximum difference between the indentation depth shown by the finite element model and that found with macroindentation testing was 5.9%, which demonstrates that the model is valid.